What is diversity worth to farmers?: November 2005, Briefs 13-18 - Smale, Melinda; King, Amanda (2005)
List of Briefs: 13. Introduction: On-farm genetic resources and economic change; 14. Traits and taxonomies: building blocks for understanding diversity; 15. Crop diversity and economic change; 16. Conservation objectives and policy trade-offs; 17. Seeds, markets, and information; 18. Targeting conservation policy.